Constitutional Challenges in the Algorithmic Society (Cambridge University Press, 2022)
The law struggles to address the constitutional challenges of the algorithmic society. This book is for scholars and lawyers interested in the intersections of law and technology. It addresses the challenges for fundamental rights and democracy, the role of policy and regulation, and the responsibilities of private actors.